Analysis of cryptocurrencies as standard financial instruments - Bartoš, Jakub (2015)
This paper analyzes cryptocurrencies as financial instruments. Firstly, we introduced the main features of cryptocurrencies and summarized the brief history. We found out that price of the most famous cryptocurrency Bitcoin follows the hypothesis of efficient markets and it immediately react on publicly announce information. Furthermore, Bitcoin can be seen as standard economic good that is priced by interaction of supply and demand on the market. These factors can be driven by macro financial development or by speculative investors, but there weren't found any significant impact of these factors on price of Bitcoin. CAPM shows the high risk of cryptocurrencies, but it could be still good instrument for diversification.